THE PATTERN OF CORRUPTION AN ERADICATION STRATEGY IN INDONESIA AS A DEMOCRATIC COUNTRY - Jiwa Muhamad Satria Nusantara (Association of Certified Fraud Examiners Indonesia Chapter, 2019)
High rates of corruption in Indonesia be the one to proof that corruption is a comprehensive type of crime. Related to that, the pattern of corruption eradication must be comprehensive, simultaneous, holistic and integrated. In its development, the pattern of eradicating corruption in Indonesia needs to be done by